Identification of aloe and other dyes by means of SERS and HPLC-DAD-MS in the embroidery of a 15th century English folded almanac. (October 2021) - Calà, Elisa; Salis, Annalisa; Damonte, Gianluca; Signorello, Stefania; Brenner, Elma; Carey, Jacqui; Aceto, Maurizio
Abstract: The folded almanac Western MS.8932 (Wellcome Collection, London), produced in England between 1387 and 1405, is a calendar with astrological tables and diagrams used by medical practitioners to harness astrological information relating to health. Apart from the great interest for its use in medicine, this object has a unique feature in its exquisite, unique embroidered binding that indicates a prestigious artefact. Considering the scarceness of information on such items, a diagnostic study on the materials used for the outstanding embroidery of MS.8932 is a unique occasion of having information on the methods of production of medieval embroideries. A diagnostic campaign has been carried out to identify the dyes used for this task and the colourants used for the illuminations, and to evaluate them with reference to their commercial value. Preliminary information on the dyes was yielded by means of UV–visible diffuse reflectance spectrophotometry with fibre optics (FORS) and spectrofluorimetry with fibre optics (FOMF). Then a final identification was yielded by micro-invasive analysis involving Surface Enhanced Raman Spectroscopy (SERS) and High Performance Liquid Chromatography-Diode Array Detector-Mass Spectrometry (HPLC-DAD-MS) [1]. Analysis on the micro samples (5–10 mm of very thin threads) taken from the embroidery revealed the presence of orchil for pink hues, indigo/madder double dyeing for purple hues, red safflower for salmon pink hues and indigo/weld double dyeing for green hues. Particularly remarkable was the additional identification of aloe in the purple threads, possibly used as mordant and/or as antibacterial agent, which evidence is the first ever recorded in such materials. This information is very important to understand the significance of the artefact and its historical-artistic location, and will allow to make comparison with similar artworks. Abstract : ∙ The folded almanac Western MS.8932 is famous for its outstanding embroidery ∙Orchil, indigo/madder, red safflower and indigo/weld were identified as dyes used for the embroidery ∙Aloe was identified, perhaps used as an antiseptic agent ∙The palette used for the illuminations, typical of 15 th -century Northern Europe, was characterised.